Aspek-aspek dalam Menyusun Bahan Ajar Komsel: Suatu Usulan bagi Gereja Penyebaran Injil Majalengka - Debi Debora Kusumawati; Joko Prihanto (Sekolah Tinggi Theologia Nazarene Indonesia, 2021)
Cell group is one of the most basic forms of service that must be developed by the church in helping the congregation it serves so that it becomes more mature and grows in the knowledge of God. In addition to praise, prayer, and worship, teaching is an important thing in the conduct of cell groups. In connection with teaching, the church must prepare teaching materials that are relevant to the needs of cell grup members. The goal is to make cell grup members more interested in participating in cell groups, and to become more mature in God and able to face the challenges of life that they are facing.The research method used is library research. This method collects data and information in the form of documents, data archives and other literature information. This paper is expected to help churches in developing cell group's services so that the church has a strong concept in compiling teaching materials that are relevant to cell group's members. This paper will discuss the nature of cell group, the importance of teaching materials relevant to cell group members, the biblical basis of teaching materials relevant to cell group members, and ends with concepts in compiling teaching materials in cell group.